ASSESSING PHYSICAL DISORDER IN URBAN NEIGHBORHOODS: RELIABILITY AND VALIDITY OF THE PARCEL MAINTENANCE OBSERVATION TOOL. Issue 1 (January 2016) - Reischl, Thomas M.; Krusky, Allison M.; Zimmerman, Marc A.; Aiyer, Sophie M.; Kruger, Daniel J.; Franzen, Susan P.; Lipton, Robert
Abstract : Research on neighborhood factors that influence health and crime often use neighborhood measures of geographic areas such as census tracts, wards, and postal sectors. These administratively defined areas, however, may mask the heterogeneity of neighborhood influences. In response to calls for more specific measures, we tested the reliability and validity of the Parcel Maintenance Observation Tool (PMOT)–a new measure of physical disorder on property parcels. The results included baseline assessments of 6134 parcels in 2 urban neighborhoods, inter‐correlations, inter‐rater reliability, and tests of concurrent validity. Most of the measures had high or adequate inter‐rater reliability. The PMOT measures differentiated between (a) parcels with occupied and unoccupied buildings and (b) vacant lots included in a property maintenance program and no‐program vacant lots. The discussion focuses on potential uses of the PMOT for understanding the effects of neighborhood physical disorder and for evaluating health promotion and crime prevention programs.